Model Pengembangan Pemberdayaan Pengetahuan (Studi pada Perpustakaan Desa Paseban, Kec. Kencong, Kab. Jember) - Anita Tri Widiyawati (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The Village Library has full responsibility in terms of empowering knowledge for the community. This is because the village library has a strategic position in rural communities. The empowerment of this knowledge is very closely related to the achievement of prosperity both materially and nonmaterial. In the empowerment of knowledge refers to the existing conditions of the village library, potential maps, and problems that exist in the Paseban Village community. This research uses a case study with a qualitative approach. Data collection techniques used are observation, interviews, documentation, audio-visual material (Creswell). Analysis of the data used is Creswell data analysis. The researcher chooses to use qualitative validity and reliability to demonstrate the validity of the data as well as the accuracy of the research results. The results of this study are that the Paseban Village Government has carried out empowerment related to tourism development, BumDes, and through the provision of the internet. However, it is not under the auspices of the village library. The empowerment carried out is partial, not centered on the village library. Paseban Village Government has not fulfilled the three aspects of empowerment, namely a) enabling, b) empowering, and c) protecting. So that there is a need to develop a model of knowledge empowerment in the Paseban Village Library, including: a) enabling (village library as a center of knowledge, village library creates an atmosphere that allows the potential of the community to develop by maximizing the function of the library; b) empowering (strengthening the village library as a center of knowledge , strengthening the village library in creating an atmosphere that enables the potential of the community to develop by maximizing the function of the library with concrete steps, the concept that is in enabling is practiced with concrete steps and the availability of infrastructure that can support the creation of community empowerment; c) protecting ( the village library as a knowledge center establishes an information center that can protect and defend the community in terms of knowledge and information related to the distribution of the results of community innovation, the village library covers everything needed community in developing welfare literacy.